Classical solvability of a problem with moving boundaries for a hyperbolic system of quasilinear equations - Andrusyak, R. V.; Burdeina, N. O.; Kirilich, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
Using the method of characteristics and the method of contracting mappings, we establish the local classical solvability of a problem for a hyperbolic system of quasilinear first-order equations with moving boundaries and nonlinear boundary conditions. Under additional assumptions on the monotonicity and sign constancy of initial data and a restriction on the growth of the right-hand sides of the system, we formulate sufficient conditions for the global classical solvability of the problem.